PROSES PERKAWINAN MENURUT HUKUM ADATDI KEPULAUAN MENTAWAI DI SEBELUM DAN SESUDAH BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Triadi Triadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Rules of conduct within marriage has been around since there were sustained indigenous community members and leaders of indigenous peoples. This rule had been developed by adjusting the rules that apply in general in the territory of the Republic of Indonesia Kesatua (national) and often with the times, science and technology.